2020
DOI: 10.3390/nano10071377
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity, Bioaccumulation and Biotransformation of Glucose-Capped Silver Nanoparticles in Green Microalgae Chlorella vulgaris

Abstract: Silver nanoparticles (AgNPs) are one of the most widely used nanomaterials in consumer products. When discharged into the aquatic environment AgNPs can cause toxicity to aquatic biota, through mechanisms that are still under debate, thus rendering the nanoparticles (NPs) effects evaluation a necessary step. Different aquatic organism models, i.e., microalgae, mussels, Daphnia magna, sea urchins and Danio rerio, etc. have been largely exploited for NPs toxicity assessment. On the other hand, alternative biologi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Several studies have reported a decrease in chlorophyll content upon exposure to uncoated AgNPs in freshwater algae C. vulgaris [ 18 , 34 ], P. oedogonia and Chara vulgaris [ 27 ], and C. reinhardtii [ 31 ], as well as vascular plants, e.g., rice [ 141 , 162 ] and A. thaliana [ 163 ]. A decline in chlorophyll content was also observed upon exposure to AgNPs stabilized with different surface coatings, e.g., in freshwater algae Scenedesmus after exposure to AgNP-PVA [ 26 ], C. vulgaris treated with AgNP-glucose [ 35 ] and AgNP-citrate [ 22 ], and in A. thaliana exposed to AgNP-citrate [ 90 ]. AgNP-induced reduction of carotenoid content has also been reported upon treatment of A. thaliana with AgNP-citrate [ 90 , 92 ] and in O. sativa exposed to uncoated AgNPs [ 141 ].…”
Section: Impact On Photosynthesismentioning
confidence: 99%
“…Several studies have reported a decrease in chlorophyll content upon exposure to uncoated AgNPs in freshwater algae C. vulgaris [ 18 , 34 ], P. oedogonia and Chara vulgaris [ 27 ], and C. reinhardtii [ 31 ], as well as vascular plants, e.g., rice [ 141 , 162 ] and A. thaliana [ 163 ]. A decline in chlorophyll content was also observed upon exposure to AgNPs stabilized with different surface coatings, e.g., in freshwater algae Scenedesmus after exposure to AgNP-PVA [ 26 ], C. vulgaris treated with AgNP-glucose [ 35 ] and AgNP-citrate [ 22 ], and in A. thaliana exposed to AgNP-citrate [ 90 ]. AgNP-induced reduction of carotenoid content has also been reported upon treatment of A. thaliana with AgNP-citrate [ 90 , 92 ] and in O. sativa exposed to uncoated AgNPs [ 141 ].…”
Section: Impact On Photosynthesismentioning
confidence: 99%
“…The authors reported a broad spectrum of genetic, molecular, cellular, morphological and behavioral effects, involving a wide range of organisms, such as algae, duckweed, amphipods, daphnids, chironomids, terrestrial plants, nematodes and earthworms. It is interesting to note that, having reported values mainly for aquatic ecotoxicity, the most sensitive test turned out to be the algae assay, and the most toxic nanomaterials were composed of silver, reinforcing the impact of the contribution by Mariano et al [4]. The other review, by Zahra et al [10], mainly focused on the aspect of environmental safety, and gave an overview of the potential exposure route of titanium dioxide nanoparticles from industrial applications to wastewater treatment, and the impact of this on the agro-environment.…”
mentioning
confidence: 79%
“…The bioaccumulation of AgNPs can occur through various routes, including ingestion, inhalation, and dermal exposure. Once inside the organism, AgNPs can interact with biological molecules and cause toxicity and adverse effects [65] [66] [67].…”
Section: Bioaccumulation Of Agnpsmentioning
confidence: 99%